Development of a Flipbook Media Featuring KAPILARA (Karakter Pilar Dua) to Foster Children’s Independence in Kindergarten - Dewi, Kustiana; Dewi, Anita Chandra; Purnamasari, Iin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aimed to develop a flipbook learning media containing Kapilara values (Karakter Pilar Dua) to foster the independent profile of kindergarten children, and to examine its validity, practicality, and effectiveness. The study employed a Research and Development (R&D) method adapted from the Borg and Gall model through seven stages: needs analysis, planning, initial product development, expert validation, limited trial, field implementation, and final revision. The population was all children in Group A of TK Intan Permai, totaling 17 children, selected using purposive sampling as the unit of analysis. Data were collected through structured interviews with the class teacher, direct observation using a behavioral checklist, expert validation sheets, parent response questionnaires, and learning documentation. Quantitative data were analyzed using descriptive percentage techniques, while qualitative data from observations and interviews were analyzed thematically. The findings revealed that material expert validation reached 94.6% and media expert validation reached 93.7%, both categorized as very valid. Practicality based on parents' responses reached 93.01%, categorized as very practical. Effectiveness results showed significant improvement in children's independent behaviors, including self-care, task completion, responsibility, and discipline. Therefore, the developed Kapilara-based flipbook media is feasible, practical, and effective for strengthening character education in early childhood institutions.